All of us? An exploration of the concept of mental health literacy based on young people's responses to fictional mental health vignettes. (29th January 2015) - Chambers, D.; Murphy, F.; Keeley, H. S.
Abstract : Objectives: Mental health literacy is increasingly referenced as a goal of mental health policy. However, the current definition of this concept has a relatively narrow focus on mental disorders. The objectives of this study were to explore mental health literacy through the use of vignettes and to begin to articulate a broader definition. Methods: Six groups of young people ( n =42) aged between 16 and 25 years old responded to open-ended questions about vignettes depicting fictional characters with diagnosable mental health problems. The responses were analysed using Foucault's governmentality theory. Results: The responses to the vignettes highlighted a range of determinants of our mental health. The young people suggested informal mental health-promoting techniques and highlighted the importance of talking. Ambiguity was reported in relation to the types of knowledge that are important in responding to mental health need. Finally, the responses were reflective of young people who are empathetic and view mental health from the perspective of our shared humanity, rather than as a marginal issue. Conclusions: As mental health literacy is increasingly becoming a goal of mental health policy, it is timely that a shared understanding of this important concept is articulated. The current definition of mental health literacy is narrow in its focus on the recognition of mental disorders. A more broad-based definition of mental health literacy should be adopted by policy makers, reflecting the full range of determinants of mental health and recognising the importance of mental wellbeing.